Pre-Election Dynamics in Yogyakarta - Sherlly Rossa; Muhammad Sidik Efendi; Lenny Aurelia Amilia; Muhammad Ali Syahadah; Stefanus Ega Panji Panuntun (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study examines electoral conflict dynamics in Indonesia's Yogyakarta Special Region, which is identified as the second-most vulnerable region nationally, with a score of 63.67% on the 2024 Election Vulnerability Index (Indeks Kerawanan Pemilu/IKP). A significant driver of this vulnerability is the recurrent conflict among political party-affiliated groups or grassroots organisations (often referred to as